Uncovering the microbial diversity of Czech Republic archives: A study of metabolically active airborne microbes - Branysova, Tereza; Petru, Nicole; Lopez Marin, Marco A; Solcova, Milada; Demnerova, Katerina; Stiborova, Hana (Heliyon, 2024)
Despite the diligent efforts of libraries, archives, and similar institutions to preserve cultural monuments, biodeterioration continues to pose a significant threat to these objects. One of the main sources of microorganisms responsible for the biodeterioration process is the presence of airborne microorganisms. Therefore, this research aims to monitor and compare outcomes of both culture-dependent (utilising various cultivation strategies) and culture-independent approaches (RNA-based sequencing) to identifying metabolically active airborne microorganisms in archives in the Czech Republic. Through this study, several species that have the potential to pose risks to both cultural heritage objects and the health of institution employees were found. Additionally, the efficacy of different cultivation media was demonstrated to be varied across archive rooms, highlighting the necessity of employing multiple cultivation media for comprehensive analyses. Of noteworthy importance, the resuscitating-promoting factor (Rpf) proved to be a pivotal tool, increasing bacterial culturability by up to 30% when synergistically employed Reasoner's 2A agar (R2A) and R2A + Rpf media. Next, the study emphasises the importance of integrating both culture-dependent and culture-independent approaches. The overlap between genera identified by the culture-dependent approach and those identified also by the culture-independent approach varied from 33% to surpassing 94%, with the maximum alignment exceeding 94% in only one case. Our results highlight the importance of actively monitoring and assessing levels of microbial air contamination in archives to prevent further deterioration of cultural heritage objects and to promote improved conditions for employees in archives and similar institutions.
Keywords: Culture-dependent approach; Illumina MiSeq; Microbial air analysis; Increasing culturability; RNA analysis